Cellulose acetate in fabrication of polymeric membranes: A review. (May 2022) - Vatanpour, Vahid; Pasaoglu, Mehmet Emin; Barzegar, Hossein; Teber, Oğuz Orhun; Kaya, Recep; Bastug, Muhammed; Khataee, Alireza; Koyuncu, Ismail
Abstract: Developing biodegradable polymers to fabricate filtration membranes is one of the main challenges of membrane science and technology. Cellulose acetate (CA) membranes, due to their excellent film-forming property, high chemical and mechanical stability, high hydrophilicity, eco-friendly, and suitable cost, are extensively used in water and wastewater treatment, gas separation, and energy generation purposes . The CA is one of the first materials used to fabricate filtration membranes. However, in the last decade, the possibility of modification of CA to improve permeability and stability has attracted the researcher's attention again. This review is focused on the properties of cellulose derivatives and especially CA membranes in the fabrication of polymeric separation membranes in various applications such as filtration, gas separation, adsorption, and ion exchange membranes. Firstly, a brief introduction of CA properties and used molecular weights in the fabrication of membranes will be presented. After that, different configurations of CA membranes will be outlined, and the performance of CA membranes in several applications and configurations as the main polymer and as an additive in the fabrication of other polymer-based membranes will be discussed. Highlights: Reviewed cellulose acetate (CA) application in fabrication of separation membranes. Different configurations of CA membranes (flat sheet, hollow and nanofiber) outlined. Concluded main findings and underlined challenging aspects of CA membranes. Application in liquid filtration, gas separation, adsorption and ion exchange membranes.